(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2025)
Adult butterflies lay their eggs on specific larval host plants, which serve as food for caterpillars after hatching. This study, conducted between January 2023 and June 2024, aimed to compile a checklist and assess the spatial distribution of butterfly larval host plants within the semi-natural campus of Jahangirnagar University (JU), Bangladesh. The research identified 107 plant species from 37 families as larval hosts for 72 butterfly species. The study area was divided into 10 sites, focusing mainly on the distribution of 12 key larval host plants due to their ecological significance and extensive use by butterflies. These key plants included Capparis zeylanica, Citrus aurantiifolia, Butea monosperma, Oryza sativa, Cassia fistula, Glycosmis pentaphylla, Calotropis gigantea, Ziziphus oenopolia, Senna tora, Polyalthia longifolia, Mimosa pudica, and Delonix regia. The findings revealed that butterflies predominantly utilized plants from the Caesalpiniaceae, Poaceae, Rutaceae, Fabaceae, and Apocynaceae families as larval hosts. These results are crucial for developing effective conservation strategies for butterflies in Bangladesh, including on the JU campus. By identifying key host plants and their distribution, the study underscores the importance of habitat restoration and the protection of native species to support butterfly populations in both natural and urban areas. Asian Australas. J. Biosci. Biotechnol. 2025, 10(1), 22-33